Laparoscopic gastric bypass with remnant gastrectomy in a super-super obese patient with gastric metaplasia: a surgical hazard? - Tartamella, Francesco; Petracca, Gabriele; Romboli, Andrea; Marchesi, Federico (Acta Biomedica Atenei Parmensis, 2018)
The endoscopic inaccessibility of the gastric remnant after Roux-en-Y gastric bypass (RYGBP) for morbid obesity represents an important issue for patients with familiar history of gastric cancer (GC) or affected by premalignant lesions, such as intestinal metaplasia. If a different bariatric procedure is contraindicated, RYGBP with remnant gastrectomy represents a reasonable alternative, significantly reducing the risk of GC but potentially increasing postoperative morbidity. For this reason, only few cases have been reported in the recent Literature and none regarding a super-super obese patient. We present the case of a 55-year-old super-super obese man with a family history of GC and antral gastritis with extensive intestinal metaplasia at preoperative upper endoscopy, who underwent laparoscopic RYGBP with remnant gastrectomy.